Coordinated control of energy storage electric brake device and generator. (June 2020) - Li, Xiaocong; Meng, Hongpei
Abstract: The application of Super Capacitor energy storage Brake Device (SCBD) in the electrical braking system of Hydrogenerator can not only assist the rapid shutdown of hydrogenerator, but also significantly provide the ability to resist large disturbance of the system, which is conducive to the improvement of the transient stability of the system. Based on the principle of capacitor energy storage, the differential algebraic model of SCBD and generator excitation and speed regulation system is derived in this paper, and the multi index nonlinear control is used to design the coordinated controller. In order to verify the effect of SCBD on generator system, three-phase short circuit simulation with and without SCBD and voltage regulation disturbance simulation are carried out. The simulation results show that the SCBD braking effect is obvious and the transient stability of the system is improved significantly.